Theoretical Study on Chemospecificity of CF3SO3CF2CF3 + F− Reactions (Journal of Atomic and Molecular Sciences, 2018)
DFT and ab initio methods are used to investigate why the reaction, C(1)F3S(2)O2O(3)C(4)F2C(5)F3 +F−, results in the S-O cleavage chemospecifically. Three SN2 channels, i.e. S-O cleavage and back- and frontsideof C-O scission are predicted to occur. The F(11) and F(12) atoms of the C(4)F2 group play the multipleroles in three paths. Multi-membered rings are formed in C-O rupture mechanisms due to the neighboringeffect. The rate of S-O scission reaction is 1031 time as large as the rates of C-O rupture reactions. It is thecombination of the irreversibility and the huge rate ratios to determine that S-O cleavage is chemospecific.This conclusion agrees well with the experimental results.